THE USE OF PORTFOLIO IN IMPROVING STUDENTS' VOCABULARY MASTERY(A QUASI-EXPERIMENTAL STUDY AT THE TENTH GRADE OF A SENIOR HIGH SCHOOL IN BANDUNG) - Fujalestari Mega Rahman, - (2011)
The present study investigates the use of portfolio in improving students' vocabulary mastery in writing skill. It is aimed to find out whether the use of portfolio improves students' vocabulary mastery and how the use of portfolio is perceived by students. The present study employed quasi-experimental design. The samples were two classes of tenth grade of one of Senior High School in Bandung. The data were gathered by administering test, classroom observation, questionnaires, and interviews. Test was analyzed by using t-test, while the result of observation, questionnaires and interviews were analyzed by using theory of portfolio proposed by Dellinger (1993). The hypothesis stated that there is no significant difference between posttest means of experimental and control group after treatment. The findings showed that tobt (1.212) did not exceed the value of tcrit (2.0021) where the α = .05 which means that the null hypothesis was not rejected. On the other hand, the use of portfolio considered to have great effects because it gave meaningful experiences and motivation in learning English vocabulary in writing skill. There might be some factors that affect the success of using portfolio in improving students' vocabulary mastery in writing skill, such as teacher and students' understanding about portfolio, the condition of the students and class, materials included in portfolio, and the use of teaching media. Therefore, those aspects need to be considered by teachers, students, and other researchers.